Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae) - Rodrigues, Henrique Miranda; Cancello, Eliana Marques (Zootaxa, 2016)
Stagmatoptera Burmeister, 1838 includes medium to large-sized (49.8–98.7mm) praying mantises distributed in the Neotropical region. They are characterized for having a central, circular spot on each forewing, and 2–4 carinae in the head’s frontal shield. This study is an updated revision of the genus on the basis of type and non-type material deposited in various scientific collections from Europe and the Americas. The following nomenclatural procedures were conducted: Stagmatoptera nova is a new junior synonym of Stagmatoptera pia, Stagmatoptera ignota as the junior synonym of Stagmatoptera femoralis, and Stagmatoptera flavipennis is reinstated as the junior synonym of Stagmatoptera supplicaria. Two new species are described: Stagmatoptera diana Rodrigues sp. n. from Colombia and Venezuela, and Stagmatoptera cerdai Rodrigues sp. n. from Trinidad & Tobago and Venezuela. Stagmatoptera now includes 14 species, two of which (Stagmatoptera abdominalis and Stagmatoptera indicator) are considered as species inquirenda. We provide detailed morphological descriptions of all species, a species-level identification key, in addition to abundant visual material to assist identification. Female genitalia, a structure seldom used for taxonomic purposes, was a useful character system to distinguish among species of the genus. Distribution maps for all species are also provided.